Optimizing the spectrum of high power narrow linewidth fiber amplifier through the same complex degree of coherence - Lai, Wenchang; Ma, Pengfei; Song, Jiaxin; Ren, Shuai; Liu, Wei; Zhou, Pu (Frontiers in Physics, 2022)
The spectra of narrow linewidth fiber amplifiers are closely related to both the stimulated Brillouin scattering (SBS) threshold in power scaling process and the combining efficiency in coherent beam combining (CBC) system. In this manuscript, the SBS thresholds of fiber amplifier with different spectral distributions (Gaussian, sinc2 and rectangular) have been compared under the same spectral complex degree of coherence (CDC), which could promise the same combining efficiency in CBC system. A SBS dynamic model is established to analyze the SBS process in fiber amplifier and a comparing experiment is also performed by measuring the SBS thresholds of different spectra that have the same CDC set to be 0.96. The FWHM linewidths of Gaussian, sinc2 and rectangular spectra are adjusted to be 1.1 GHz, 0.5 GHz and 1.06 GHz, respectively. The corresponding SBS thresholds are measured to be 108 W, 77 W, and 135 W. By contrast, the rectangular spectra could have most excellent capacity on improving SBS threshold in fiber amplifier under the same combining efficiency in CBC system. Overall, it could provide a feasible method on spectra designing in high power narrow linewidth fiber amplifiers used in CBC system.